1982
DOI: 10.1159/000117895
|View full text |Cite
|
Sign up to set email alerts
|

Failure to Detect Immunologic Stigmata in Schizophrenia

Abstract: The sera of 17 patients with acute or chronic schizophrenia were tested for antibodies to a human brain extract or to Molt cells; a human T-cell line, with negative results. The level of in vivo lymphocyte stimulation was investigated by determination of the proportion of peripheral blood lymphocytes in the G1, S or G2 + M phases of the cell cycle and by their uptake of 3H-thymidine. There was no sign of increased lymphocyte mitotic activity by these two tests. Therefore, immunologic stigmata could not be dete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
1

Year Published

1989
1989
2009
2009

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 4 publications
(7 reference statements)
0
2
0
1
Order By: Relevance
“…The first steps to understanding how antigen-antibody pathology might play in mental illness has been established by animal research (Williams and Schupf, 1977), which is questionably relevant to human pathophysiology. In clinical research, while some found serum antibrain antibodies in 28-95% of studied schizophrenics (Kuznetoza and Semenov, 1961;Fessel, 1962;DeLisi et al, 1985;Henneberg et al, 1994), others were unable to reproduce these findings (Rubin, 1965;Logan and Deodhar, 1970;Ehrnst et al, 1982).…”
Section: Limitations and Future Workmentioning
confidence: 97%
“…The first steps to understanding how antigen-antibody pathology might play in mental illness has been established by animal research (Williams and Schupf, 1977), which is questionably relevant to human pathophysiology. In clinical research, while some found serum antibrain antibodies in 28-95% of studied schizophrenics (Kuznetoza and Semenov, 1961;Fessel, 1962;DeLisi et al, 1985;Henneberg et al, 1994), others were unable to reproduce these findings (Rubin, 1965;Logan and Deodhar, 1970;Ehrnst et al, 1982).…”
Section: Limitations and Future Workmentioning
confidence: 97%
“…The first steps to understanding how antigen-antibody pathology might play in mental illness has been established by animal research [69], which is debatably relevant to human pathophysiology. In clinical research, while some found serum antibrain antibodies in 28-95% of studied schizophrenics [32] [18] [12] [25], others were unable to reproduce these findings [52] [37] [16].…”
Section: The Limits and Advantages Of Modelingmentioning
confidence: 99%
“…Eine erniedrigte Aktivität der Killerzellen, die als Streßphänomen interpretiert wurde (DeLisi u. Wyatt, 1982; Glaser et al, 1986;Sasaki et al, 1994), findet sich ebenso wie eine Aktivität im Normalbereich (Schindler et a1., 1986;Resch et al, 1988). Auch die Untersuchung der Immunglobuline führte zu unterschiedlichen Ergebnissen: Während einige Autoren keinen Unterschied zwischen schizophren Erkrankten und Gesunden fanden (DeLisi, 1986;Ehrnst et al, 1982), ließen sich auch erhöhte (Reichelt u. Landmark, 1995) und erniedrigte Immunglobulinspiegel darstellen (Sasaki et al, 1994).…”
unclassified